THE EFFECT OF STRATEGIC MANAGEMENT ON INDUSTRIAL ESTATE POLICY (CASE STUDY: INDUSTRIAL ESTATE OF SEMARANG CITY) - Andi Kurniawati SE. MM.; Kasno SE. M.Si (Universitas Islam Lamongan, 2022)
Government policy can be implemented if it has valid data which explain the business field, address, owner's name and other data. The availability of valid and updated data will greatly assist the government in preparing an improvement program for the industrial sector.Based on the results of the calculation of the r test (correlation test), the variable area of land potential for industrial areas and the variable distance to the harbor and the center of city obtained a value of r count 0.487 <r table 0.95 and r count 0.914 <r table 0.95. Based on the results of the calculation of the t test (significance test), the variable area of land potential in the industrial area and the variable distance to the harbor and center of city obtained a value of t count 0.788 <t table 4.303 and t count 3.177 <t table 4.303.It is concluded that there is a positive correlation between the area of land potential and the distance between industrial estates to the harbor and center of city with industrial estate policies..